LIBERTY INNOVATION (INFORMATION TECHNOLOGY-BASED LITERACY) AS A SCHOOL LEARNING TOOL AT STATE MIDDLE SCHOOL 2 CISAUK, TANGGERANG REGENCY - Rosidah (Inovbook, 2023)
This research is about a digital innovation called LIBERTI (Information Technology-Based Literacy) as a school learning tool at SMP Negeri 2 Cisauk. This study was conducted by the Regional Government of Tangerang Regency. This research is important and relevant because it looks at the condition of students at SMP N 2 Cisauk, Tangerang Regency. In addition, this research is a form of local government efforts in improving the quality of education in the era of the Industrial revolution 4.0. It is hoped that it will facilitate the way educators teach and learn how to learn. The population in this study are regions that have implemented policies or innovations in the digital and education fields. While the sample in this study is the innovation